Pemahaman Masyarakat Terhadap Lailah al-Qadr di Desa Teratai: Kajian Living Qur’an - Armawati Armawati; Sulaiman Ibrahim; Muhammad Rusli (Program Studi Ilmu Al-Quran dan Tafsir, 2022)
This study aims to find out how the Gorontalo community, especially Lotus village, understands lailah al-qadr and the culture of the Gorontalo community when welcoming lailah al-qadr. So that in this study a formulation of the problem was formed: How is the interpretation of the Qur’an about lailah al-qadr? How is the culture of the community in welcoming and commemorating lailah al-qadr? What is the public's understanding of lailah al-qadr? The method used in this study is the tahli>li> method and uses a qualitative descriptive method using the interpretation approach and the anthropological approach of the Qur’an. Data collection techniques in this study are the results of interviews, observations, and documentation. With data analysis techniques, namely analysis by collecting data, reducing data, displaying data, and drawing conclusions or verification. The results of this study show that, the people of Gorontalo, especially Lotus village, understand lailah al-qadar with the descent of angels to the earth to bring blessings. The community also welcomed it with the celebration of Tumbilotohe (night culture of installing lights). This night culture of lamp tide is a culture that is hereditary and continues to be maintained today. This tumbilotohe is held 3 days before Ramadan ends, namely on the 27th night to the 29th night. On the 30th night or coinciding with the eve of the holiday, the lights are turned off. As a society that lives in the millennial era, we should continue to maintain and preserve the existing culture. So as not to be displaced by the development of the times and technological advances. Moreover, in celebrating the night of the lamp, it has religious values, such as improving the quality of worship on the days leading up to the end of Ramadan.